Evaluation of Software Development Stages for Turkish Cypriot Companies - Koru, Begüm (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
process is a set of activities that are used to produce software. The presentation of a simplified software process is shown in a special perspective such as workflow, data flow and role-action. There are some models designed to follow during this process which helps software improvement such as Waterfall, Spiral, Agile, Scrum and etc. To achieve competitiveness, Capability Maturity Model Integration (CMMI) is another important process model that should be used by companies. For this study, the aim is to find out the properties of the software sector in Turkish Republic Northern Cyprus (TRNC) and investigate how companies handle their software management process. The 11 companies in TRNC chosen have shared their experience on sector issues. Each of them has given details about their working areas, team, structures and models that are used, the development environment and maintenance policies. They have also shared their opinions about the software sector in TRNC, the problems and shortcomings of this sector and what has to be done to improve it. Common and contradictory points that are shared by these companies are determined. The results of our analyses showed that the informatics sector in TRNC has some problems and shortcomings. With the recommendations stated, these problems can be eliminated and the industry can be improved. Keywords: Software process, software process models, CMM, CMMI, the TRNC software sector.

ÖZ: Yazılım süreci, yazılım üretmek için kullanılan bir dizi aktivitedir. Basitleştirilmiş bir yazılım sürecinin gösterimi, iş akışı, veri akışı ve rol eylemi gibi özel bir bakış açısıyla gösterilir. Şelale, Spiral, Çevik, Scrum gibi yazılım iyileştirmeye yardımcı olan bazı yazılım geliştirme yaşam dairesi modelleri vardır. Rekabetçiliği sağlamak için şirketler tarafından kullanılması gereken diğer önemli bir süreç modeli ise Tümleşik Yetenek Olgunluk Modeli (CMMI)’dir. Bu çalışmadaki amaç KKTC'deki yazılım sektörünü ve şirketlerin yazılım yönetim süreçlerini nasıl yürüttüğünü incelemektir. Seçilen 11 şirket bu konudaki deneyimlerini paylaşmıştır. Her biri, çalışma alanları, ekibi, yapıları ve kullanılan modelleri, geliştirme ortamı ve bakım politikaları hakkındaki detayları paylaşmıştır. KKTC'deki yazılım sektörü ile ilgili görüşlerini, sektörün sorunlarını ve eksikliklerini ve bunu iyileştirmek için neler yapılması gerektiği hakkındaki görüşlerini de sunmuşlardır. Daha sonrasında bu şirketler tarafından paylaşılan ortak ve çelişen noktalar tespit edilmiştir. Yapılan çalışma sonucunda elde edilen analizlerin sonuçları, KKTC'deki bilişim sektörünün bazı sorun ve eksikliklere sahip olduğunu göstermektedir. Önerilecek tavsiyelerle bu sorunlar ortadan kaldırılabilir ve endüstri gelişebilir. Anahtar Kelimeler: Yazılım süreci, yazılım süreç modelleri, CMM, CMMI, KKTC yazılım sektörü.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2017. Supervisor: Prof. Dr. Hadi Işık Aybay.
Keywords: Computer Engineering; Computer software-Cyprus (Turkish Republic of Northern Cyprus, 1983-); Software process; software process models; CMM; CMMI; the TRNC software sector